Pauline Letters: Texts @ Contexts - Goh, Menghun (Texts Contexts, 2024)
In this volume contributors from various social locations in North America, Asia, Europe, and Australia analyse and interpret Pauline letters. Engaging both the biblical text and the lives and contexts from different sociocultural, religious, methodological perspectives, each contributor demonstrates the dynamic interaction between text and context in their understanding and explanation of the text. The first part of the volume highlights the hermeneutical focus in interpretation. That is, how a certain chosen worldview (e.g., Lutheran liturgical worldview) affects one's decision in prioritizing a certain textual dimension and level instead of others. Part Two elucidates how even a technical analysis of the text (e.g., epistolography) is context-oriented. Part Three shows how such a contemporary contextual interpretation is also an intercontextual and intertextual interpretation that entails intersectional and global-local experiences